Implementasi KKN Internasional melalui Video Korporat Surprising Kalumpang sebagai Upaya Promosi Wisata Lokal di Hulu Selangor, Malaysia - Aryandani, Rian; Rajendra, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2026)
Kalumpang in Hulu Selangor, Malaysia, holds immense tourism potential that remains underpromotion, spanning natural scenery, multicultural heritage, and unique historical legacy. This gap caught the attention of UNNES students through the KKN Mendunia program, a cross-border learning initiative positioning students as agents of global change. Using the Ipteks Diffusion method, the team produced a video titled